2012
DOI: 10.9734/ejmp/2012/1059
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Studies of Iron Chelation Activity of Purified Active Ingredients Extracted from Triticum aestivum Linn. (Wheat Grass)

Abstract: Objective: Seven to eight days germinated plants of Triticum aestivum (wheat grass) are a rich source of vitamin A, C, calcium, magnesium, phosphorus, potassium, sodium, sulphur, cobalt, zinc and protein. Traditionally the aqueous extract of T. aestivum was reported to be used as a health tonic in folk and ayurvedic medicine. We previously reported that aqueous extract of T. aestivum was found to reduce the blood transfusion requirement in iron overloaded Thalassemia and Myelodysplastic syndrome patients. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…A very few publications are available in literature on nutritive and antioxidant properties of wheatgrass juice where it is reported that these extracts contain high levels of antioxidants and inhibit the DNA oxidative damage and are effective in suppressing the superoxide radical (Kulkarni et al, 2006;Rana, 2011). It has also shown antimutagenicity (Alitheen et al, 2011;Arya and Kumar, 2011), antimicrobial (Ashok, 2011;Pallavi et al, 2011;Das et al, 2012), antiallergic (Padalia et al, 2010) and diuretic (Popovič et al, 2014) properties. Wheatgrass was also reported to be helpful incuring certain diseases such as thalassemia (Singh et al, 2010), distal ulcerative colitis, anaemia, diabetes, eczema, constipation, and ulcerative…”
Section: Introductionmentioning
confidence: 99%
“…A very few publications are available in literature on nutritive and antioxidant properties of wheatgrass juice where it is reported that these extracts contain high levels of antioxidants and inhibit the DNA oxidative damage and are effective in suppressing the superoxide radical (Kulkarni et al, 2006;Rana, 2011). It has also shown antimutagenicity (Alitheen et al, 2011;Arya and Kumar, 2011), antimicrobial (Ashok, 2011;Pallavi et al, 2011;Das et al, 2012), antiallergic (Padalia et al, 2010) and diuretic (Popovič et al, 2014) properties. Wheatgrass was also reported to be helpful incuring certain diseases such as thalassemia (Singh et al, 2010), distal ulcerative colitis, anaemia, diabetes, eczema, constipation, and ulcerative…”
Section: Introductionmentioning
confidence: 99%
“…Curcuminoids have been shown to bind in vitro and alleviate toxicity in thalassemic mice [31,32]. T h e i r o n c h e l a t i n g a c t i v i t y o f A f r i c a n w a l n u t (Tetracarpidium conophorum) and wheat grass (Triticum aestivum) extracts have been studied and the results suggest this may have potential for iron overload in thalassaemia patients [33][34][35]. The African walnut contains a number of phenolic compounds which are believed to chelate to iron or copper [34].…”
Section: Iron Chelatorsmentioning
confidence: 99%
“…T h e i r o n c h e l a t i n g a c t i v i t y o f A f r i c a n w a l n u t (Tetracarpidium conophorum) and wheat grass (Triticum aestivum) extracts have been studied and the results suggest this may have potential for iron overload in thalassaemia patients [33][34][35]. The African walnut contains a number of phenolic compounds which are believed to chelate to iron or copper [34]. The active chelators in wheat grass appear to be derivatives of mugineic acid, 3-hydroxy-mugineic acid and 2′deoxy-mugineic acid [35].…”
Section: Iron Chelatorsmentioning
confidence: 99%
“…It is also known as green blood because it enhances the production of red blood cells (Grunewald 2009). It lowers the blood pressure (Locniskar 1988), revitalizes energy (Kulkarni et al 2006), produces the required efficacy against diabetes (Samagandi et al 2012), purifies the body, aids weight loss, possesses antioxidant property (Kulkarni et al 2006;Siener et al 2006;, fights against free radicals (Borek 2002;Kulkarni et al 2006), detoxifies (Das et al 2012) and promotes healthy skin.…”
Section: Introductionmentioning
confidence: 99%